The Role of the Public Prosecutor in settlement of Child Cases Through Diversion at the Purwokerto District Attorney - Fitri Viana Sari (Faculty of Law Universitas Muhammadiyah Purwokerto, 2020)
Wherever possible, the child is avoided from examination in court. As long as it fulfills the conditions specified, juvenile criminal cases must be resolved through Diversion. The Indonesian Child Protection Commission states that there are 7000 cases of children facing court proceedings every year. This study aims to determine the role of the public prosecutor in resolving child cases through Diversion and the obstacles to implementing Diversion at the Purwokerto District Attorney. The method used is normative juridical, namely researching library materials or secondary data by searching for regulations related to the problems in this study. The results of this study 1) The role of the Public Prosecutor in resolving child cases through Diversion at the Purwokerto District Attorney's Office is to act as a mediator. If the Diversion does not reach an agreement, the Public Prosecutor shall make an official report declaring the diversion process failed and transfer the case to the District Court. On the other hand, if the Diversion is successful, the Public Prosecutor makes an official report and then submits it to the District Court. 2) The Public Prosecutor's constraints in resolving child cases through Diversion are the unclear regulations regarding the guidelines for implementing diveri at the beginning of the enactment of Law Number 12 of 2012 Regarding the Juvenile Criminal Justice System until finally, in 2015, the government issued the Regulation of the Attorney General of the Republic of Indonesia Number PER-006/JA/04/2015 concerning Guidelines for Implementing Diversion at the Prosecution Level. If the victim was not cooperative, the perpetrator could not fulfill the request for compensation from the victim. That culture develops in society that perpetrators of crimes must be tried and sentenced to prison regardless of whether the perpetrator is a minor, hindering the diversion process's implementation.Keywords: Prosecutor's Role, Children, Diversion